Systematic Literature Review on Application of Biotechnology on Salak (Salacca spp.) Breeding Program Acceleration: The Unsolved Mysteries - Prihatini, Riry; Marlina, Leni; Hariyanto, Bambang; Mayura, Eliza; Sukartini, Sukartini (AGRIVITA Journal of Agricultural Science, 2024)
Salak (Salacca spp.) is a tropical fruit native to Indonesia that has various benefits for human health. Salak breeding programs to produce new superior varieties are constrained by the long-life cycle of the plant, making it difficult to select the desired traits. Few systematic literature reviews have been conducted on salak breeding. The present article was written to analyse the existing literature on application of plant biotechnology on salak breeding program. Guided by the PRISMA Statement (Preferred Reporting Items for Systematic reviews and Meta-Analyses) review method, a systematic review of the Scopus and Google Scholar databases identified 42 eligible related studies. The literature screening process was conducted using Mixed Method Appraisal Tool, whereas the bibliometric network analysis was conducted using VOS viewer software. Further review of these articles resulted in three main themes – genomics, metabolomics, and tissue culture. These three themes produced a total of eight sub-themes. The application of biotechnology on salak plant breeding are still limited, the genomic and metabolomic of this tropical fruit are still a mystery. Several future perspectives for salak’s breeding program includes deeper study on the plant’s genomic aspects, such as genotyping by sequencing, genome mapping, and development molecular marker assisted selection.